Pure Laparoscopic Versus Open Liver Resection in Treatment of Hepatolithiasis Within the Left Lobes. Issue 5 (October 2015) - Ding, Guoqian; Cai, Wang; Qin, Mingfang
<x xml:space="preserve">Abstract</x> Objective: The application of laparoscopic technology to liver surgery has been developing rapidly, yet very few studies have been conducted to compare the outcomes between open and laparoscopic liver resections. So little is known about their advantages and disadvantages. The aim of this prospective randomized study was to compare the outcomes between laparoscopic and open liver resection in treatment of hepatolithiasis within the left lateral lobes. Patients and Methods: Between January 2010 and May 2013, 98 patients with hepatolithiasis within the left lateral lobes diagnosed by preoperative computed tomography and magnetic resonance cholangiopancreatography were randomized into open group and laparoscopic group. Each group had 49 patients. We compared the operation time, the amount of bleeding, the length of their stay in hospital, and complications. Results: Of the laparoscopic group, 2 patients were converted to open surgery. No fatal complication occurred in either the open group or the laparoscopic group. There was no statistically significant difference in the complications between the 2 groups (4.08% vs. 6.12%, P=0.64), but the operating time, the amount of bleeding, and the length of stay in hospital were significantly shorter in the laparoscopic group than in the open group (P<0.05). Conclusions: Laparoscopic liver resection displays similar safety and feasibility for hepatolithiasis within the left lateral lobes, and they were also similar with respect to the overall complications, but the laparoscopic group has an advantage in the operating time, the amount of bleeding, and the length of their staying in hospital. It is, however, agreed between the authors of this paper that further studies with larger number of patients and longer follow-up observations are necessary to make a definitive conclusion.